L’Unheimlichkeit della poesia e il suo ruolo nella comunità. Gadamer e Derrida in dialogo - Romagnoli, Elena (Aesthetica Preprint, 2021)
This contribution aims to discuss the readings of the artistic experience presented by Gadamer and Derrida, showing their fundamental agreement on the idea of poetry as a unique phenomenon that is at the same time intrinsically repeatable. This conception is able to overcome the limitations of Heidegger’s idea of the poet as a mystical-prophetic figure as well as to rethink the role of poetry in the community. Furthermore, Gadamer’s and Derrida’s conceptions are capable to account for the peculiar participation of the public in contemporary works of art, as it emerges from their interpretations of Celan’s poetry.